FORMATION AND REALIZATION OF SOCIO-ECONOMIC POLICY IN MICROREGION ON DECENTRALIZATION (Regional aspects of productive forces development of Ukraine, 2019)
The article outlines the main factors of the formation and implementation of regional policy at the micro-region level in order to ensure the proper economic capacity of the territorial community.In the conditions of decentralization, the local self-government bodies are almost independent and fully responsible for the state of socio-economic development of communities.The main factors that should be taken into account in the development of socio-economic regional policy at the level of the united territorial communities are the following: the state of the regional labor market development; the state of use of internal regional factors for the development of productive forces; the state of the road infrastructure; social needs of the region population.It is necessary to implement the regional policy of the united territorial communities for the sake of solving complex problems on the basis of the development strategy of this community, in particular with a view of ensuring the financial autonomy and economic capacity.In the developing of the socio-economic development strategy of the microregion, the main principles should be: focusing on the needs and interests of people living in the microregion; longterm vision of the territory development; a comprehensive and holistic approach of solving current problems; grounding on a comprehensive analysis of the status of local regional development; active and effective public participation.The key components of the socio-economic development strategy of the micro-region should be: assessment of its resource potential; analysis of the demographic situation in the microregion; analysis of labor potential and its employment; modern state of micro-region economic development; study of the state infrastructure available to it; a generalized analysis of the socio-economic situation in the microregion and challenges in the future; priority directions of microregiondevelopment; regional micro-region development programs.